Numerical tests on pattern formation in 2d heterogeneous mediums: an approach using the schnakenberg model (2012)
This paper presents several numerical tests performed on Turing space when spatial parameters in reaction-diffusion equations changes. The tests are performed in 2D on square units in which we perform subdivisions (subdomains). In each subdomain we set parameters that correspond to different wave numbers and therefore presents a heterogeneous medium. Each wave number is predicted by the linear stability theory and correspond to different Turing patterns. The reaction equation chosen is that of Schnakenberg. The results show complex patterns that mix bands and spots, as well as patterns that do not correspond with the original patterns that could be found independently in each subdomain.